Exegesis Integrative Review of Salvation Because The Love Of God Is The Basic of The Church As The Unity of The Body of Christ (Ephesians 2:11-22) - Tonny Andrian (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
The subject of the unity of the church has appeared several times during the period of church history as a major subject. Even in the 20th century, differences of opinion on the subject of unity led to divisions. This point cannot be ignored. That is why the researcher conducted an integrated exegessa study on the meaning of the Church as the unity of the body of Christ Ephesians 2: 11-22. Ephesians 2: 11-22 is not a separate passage, but integrative, with other passages in the book of Ephesians. (this would be integrative both with Ephesians 2: 1-10 and Ephesians 4: 1-6) The conjunction